Sendingwerk in die landdrosdistrikte Stellenbosch en Tulbagh (sedert 1822 Worcester), 1799-1930 - De Jongh, P. S. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 1968.